2001
DOI: 10.1182/blood.v97.1.147
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired survival of bone marrow hematopoietic progenitor cells in cyclic neutropenia

Abstract: Cyclic neutropenia (CN) is a congenital hematopoietic disorder characterized by remarkably regular oscillations of blood neutrophils from near normal to extremely low levels at 21-day intervals. Recurring episodes of severe neutropenia lead to repetitive and sometimes life-threatening infections. To investigate the cellular mechanism of CN, the ultrastructure and the proliferative and survival characteristics of bone marrow-derived CD34(+) early progenitors, CD33(+)/CD34(-) myeloid progenitors, and CD15(+) neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 35 publications
1
54
0
2
Order By: Relevance
“…This marrow abnormality is due to defective neutrophil formation with interruption of cell production at the promyelocyte-myelocyte stage, the stage in neutrophil development when the enzyme neutrophil elastase is normally synthesized and packaged in the neutrophil granules [18]. Several recent studies now link the finding of "maturation arrest" and the mutations in ELA2 gene.…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations
“…This marrow abnormality is due to defective neutrophil formation with interruption of cell production at the promyelocyte-myelocyte stage, the stage in neutrophil development when the enzyme neutrophil elastase is normally synthesized and packaged in the neutrophil granules [18]. Several recent studies now link the finding of "maturation arrest" and the mutations in ELA2 gene.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Examination of marrow samples by electron microscopy show cytoplasmic blebbing and autophagy of debris of degenerating neutrophils, features that are not observed in normal marrow samples [18]. Annexin 5 staining and fluorescence activated cell sorting (FACS analysis) show that patients have degenerating cells with exposure of phospholipids on the surface of cells which are usually maintained on the cells' internal surfaces [18]. Transfection studies utilizing several cell lines, as well as normal human CD34 cells, showed that expression of mutant ELA2 leads to the unfolded protein response with up-regulation of the master endoplasmic reticulum chaperone referred to as BiP, a molecular correlate of accelerated apoptosis.…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Assay of growth inhibition of C. albicans by BMC was performed on the basis of a crystal violet (CV) staining method, as described previously (13). BMC (4ϫ10 4 or 8ϫ10 4 cells) were seeded in the wells of a 96-well flatbottomed microplate with 100 µl of complete medium. After pre-incubation with a designated concentration of rhG-CSF at 37 C for 24 hr, C. albicans suspension (5ϫ10 2 cells) in 50 µl of complete medium was added to each well.…”
Section: Methodsmentioning
confidence: 99%